STRENGTH TEST AND RELIABILITY EVALUATION OF 20CRNIMO MATERIAL (MT) - GUO YuLiang; WEI BingYang; GU DeWan; WANG YongQiang; CAO XueMei (Jixie qiangdu)
Low carbon alloy steel 20CrNiMo is a kind of high strength surface hardening material which was commonly used as high-quality gears. After surface nitriding, carburizing or carbonitriding quenching treatment, it has good tooth surface hardness and tooth root toughness. According to the relevant national standards, a number of material test bars had been designed and carried out, the tensile strength and tensile fatigue strength date of material had been obtained. The lognormal distribution and two parameters Weibull distribution were used to fit and test the testing data, and the R-S-N curves of materials with the different confidence levels were obtained by calculating the probability distribution function. The fatigue life data of the material was more suitable for the lognormal distribution.